After genocide : bringing the devil to justice / bringing the devil to justice - Smith, Adam M., 1974- (Amherst, N.Y. : Prometheus Books, 2009)
"Imagine a criminal justice system that achieves fewer than five convictions per year and spends more than $20 million on each one. By some measures, this would make it the least efficient prosecutorial system in recorded history. Imagine that this same system consistently runs the risk of creating rather than deterring crimes, with few victims or perpetrators believing that it provides fairness, equity, or justice. For many in Rwanda, the former Yugoslavia, Sierra Leone, and elsewhere, this is the reality of the justice that the world community has provided for them in its international criminal tribunals." "How did one of the bravest and most optimistic expressions of post-Cold War global power - the provision of justice to those victimized by atrocious crimes - slip into a system in which so many doubt justice is being done, a system that may well exacerbate the problems it was designed to fix?" "Adam M. Smith, an international lawyer and the son of a Holocaust refugee, has worked on international justice in The Hague, the Balkans, Africa, and Asia. He comprehensively examines the complex, politicized world of international criminal justice from the ground up - from the perspective of those victims and survivors in whose name justice is being provided. Smith reviews the shortcomings of the international justice system in several hot spots." "Are other options available to provide justice without the devastating side effects? Smith illustrates the viability of a counterintuitive, yet historically tested, solution to dealing with genocide and other atrocities: placing the victims, survivors, and perpetrators center stage and entrusting the challenging and potentially destabilizing work of war crimes justice to the very states affected by the crimes." "After Genocide is indispensable reading for voters, policymakers, and citizens, as well as lawyers, academics, and human rights activists who hope that "never again" can become more than a platitude." --Book Jacket.
From Budapest to Bondi to Bosnia : an unlikely war crimes journey -- An odd, misguided debate : is it really international justice or no justice? -- Left behind -- The politics of hell : what happened? -- Falling on deaf ears (part I) : international justice from the ground up -- Falling on deaf ears (part II) : "unfair and unhelpful" -- The International Criminal Court and the limits of international justice -- They say it can't be done -- Croatia : justice in the shadow of the Hague.
Includes bibliographical references (p. 347-408) and index.
Keywords: International Criminal Court; Justice, Administration of -- International cooperation; International criminal courts; Genocide